Proteome analysis of Physcomitrella patens exposed to progressive dehydration and rehydration - Cui, Suxia (Journal of experimental botany, 2012)
Physcomitrella patens is an extremely dehydration-tolerant moss. However, the molecular basis of its responses to loss of cellular water remains unclear. A comprehensive proteomic analysis of dehydration- and rehydration-responsive proteins has been conducted using quantitative two-dimensional difference in-gel electrophoresis (2D-DIGE), and traditional 2-D gel electrophoresis (2-DE) combined with MALDI TOF/TOF MS. Of the 216 differentially-expressed protein spots, 112 and 104 were dehydration- and rehydration-responsive proteins, respectively. The functional categories of the most differentially-expressed proteins were seed maturation, defence, protein synthesis and quality control, and energy production. Strikingly, most of the late embryogenesis abundant (LEA) proteins were expressed at a basal level under control conditions and their synthesis was strongly enhanced by dehydration, a pattern that was confirmed by RT-PCR. Actinoporins, phosphatidylethanolamine-binding protein, arabinogalactan protein, and phospholipase are the likely dominant players in the defence system. In addition, 24 proteins of unknown function were identified as novel dehydration- or rehydration-responsive proteins. Our data indicate that Physcomitrella adopts a rapid protein response mechanism to cope with dehydration in its leafy-shoot and basal expression levels of desiccation-tolerant proteins are rapidly upgraded at high levels under stress. This mechanism appears similar to that seen in angiosperm seeds